(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The formation of Cu2+ : Tryptophan (Trp) = 1 : 1 complex, which acts as a model catalyst for decomposition of cumene hydroperoxide (ROOH) in H2O+Cu2++Trp+ROOH system, has been confirmed via kinetic study in aqueous solution at pH > 7. Kinetic equation of single catalytic decomposition reaction of ROOH under the influence of [CuTrp]+ complex was derived: W0= –d[ROOH]0/dt=Kcat[Cu2+]0[Trp]0[ROOH]0= Keff [ROOH]0. The temperature dependence of the effective rate constant Keff (Keff = Kcat[Cu2+]0[Trp]0 = const) for ROOH decay in the temperature range from 323 to 343 K can be expressed by Arrhenius equation (Keff is in kJ/mol): Keff =(7.45 ± 0.02) ·106exp[–(56.5 ± 0.2)/RT] 1/min.